(untitled) (Journal of the College of Basic Education, 2023)
The aim of this research is to identify the effectiveness of using the Photoshop program in teaching mathematics in developing thinking processes among sixth grade students. The study sample was selected from students in the two primary schools of Al-Manhal and Al-Modon City Primary School for the academic year (2021-2022), due to the availability of classes for the sixth grade of primary school in these schools. A female student and the other is an experimental group of 19 male and female students. The results of data processing showed the effectiveness of using Photoshop in